Human rDNA copy number is unstable in metastatic breast cancers. Issue 1 (1st February 2020) - Valori, Virginia; Tus, Katalin; Laukaitis, Christina; Harris, David T.; LeBeau, Lauren; Maggert, Keith A.
ABSTRACT: Chromatin-mediated silencing, including the formation of heterochromatin, silent chromosome territories, and repressed gene promoters, acts to stabilize patterns of gene regulation and the physical structure of the genome. Reduction of chromatin-mediated silencing can result in genome rearrangements, particularly at intrinsically unstable regions of the genome such as transposons, satellite repeats, and repetitive gene clusters including the rRNA gene clusters ( rDNA ). It is thus expected that mutational or environmental conditions that compromise heterochromatin function might cause genome instability, and diseases associated with decreased epigenetic stability might exhibit genome changes as part of their aetiology. We find the support of this hypothesis in invasive ductal breast carcinoma, in which reduced epigenetic silencing has been previously described, by using a facile method to quantify rDNA copy number in biopsied breast tumours and pair-matched healthy tissue. We found that rDNA and satellite DNA sequences had significant copy number variation – both losses and gains of copies – compared to healthy tissue, arguing that these genome rearrangements are common in developing breast cancer. Thus, any proposed aetiology onset or progression of breast cancer should consider alterations to the epigenome, but must also accommodate concomitant changes to genome sequence at heterochromatic loci.